2022
DOI: 10.1609/aaai.v36i7.20715
|View full text |Cite
|
Sign up to set email alerts
|

RareGAN: Generating Samples for Rare Classes

Abstract: We study the problem of learning generative adversarial networks (GANs) for a rare class of an unlabeled dataset subject to a labeling budget. This problem is motivated from practical applications in domains including security (e.g., synthesizing packets for DNS amplification attacks), systems and networking (e.g., synthesizing workloads that trigger high resource usage), and machine learning (e.g., generating images from a rare class). Existing approaches are unsuitable, either requiring fully-labeled dataset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Liu et al [198] studied how well GAN can approximate the target distribution under various notions of distributional convergence. Lin et al [199] showed that GAN-generated samples inherently satisfy some (weak) privacy guarantees under certain conditions. Another study offers a theoretical perspective on why GANs sometimes fail for certain generation tasks, in particular, sequential tasks such as natural language generation [200].…”
Section: Recent Theoretical Advancements Of Ganmentioning
confidence: 99%
“…Liu et al [198] studied how well GAN can approximate the target distribution under various notions of distributional convergence. Lin et al [199] showed that GAN-generated samples inherently satisfy some (weak) privacy guarantees under certain conditions. Another study offers a theoretical perspective on why GANs sometimes fail for certain generation tasks, in particular, sequential tasks such as natural language generation [200].…”
Section: Recent Theoretical Advancements Of Ganmentioning
confidence: 99%
“…Thus, both parties improve their respective skills over time. As the generator does not have access to the training data and, thus, creates entirely new data points, this model architecture implies privacy [8].…”
Section: Generative Adversarial Networkmentioning
confidence: 99%
“…Hence, it is often challenging to build appropriate machine learning algorithms as data availability remains an issue [7]. The creation of synthetic data through generative adversarial networks (GAN) could be one solution to tackle this field of problems connected to EHR as the creation of synthetic data through the application of GANs not only implicates privacy [8] but is also able to remedy data scarcity or an imbalance in data sets [9]. Introduced in 2014 by Goodfellow et al [10], the research related to GANs has surged since then.…”
Section: Introductionmentioning
confidence: 99%
“…In , a supervised contrastive learning method is designed that adds a loss term between the samples and the pre-defined class centers to regularize representation learning with geometric priors. CMO (Park et al 2022) and RareGAN (Lin et al 2022) are the latest data-balancing methods for deep imbalance learning. But their settings are different from ours, since we deal with labeled data and aim to improve the performance of imbalance learning through self-training.…”
Section: Related Workmentioning
confidence: 99%